Tá ligado? : usos e sentidos da gíria entre estudantes do ensino médio - Silva, Rômulo Felipe da (2009)
This study aims to find the use of slang among high school students in a private school in the city of Recife. It has been assumed criptologic aspect of the use of this, as a representative of a variation linguistic identity of social group by age, as opposed to the group of adults. The identity of the teenager was also set by its language. As method will be conducted 12 interviews semidirectives, with students of both sexes, aged from 16 to 18 years old and recorded by electronic way, a college network of private schools. Through an analysis of content, there will be a lifting of slang used according the students by sex, an investigation of the significance of their use among the subjects in the daily school and extra-school, and also identified the context of use in the socio-cultural environment of the student. It will involve situations as a break from class, be in the classroom without a teacher, be in a shopping center, the beaches, among others. This research raises contributions to the thinking and perception about the use of idioms and their context of occurrence among teenagers